THE POBIDYNSKI NOBLE FAMILY IN SANOK LAND IN THE 16th CENTURY (ACCORDING TO THE RECORDS OF THE SANOK CASTLE AND LAND COURTS) - LYSEYKO , Yaroslav; IARMOLENKO , Oleksandr (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to reconstruct the genealogy, property, and social status of the Pobidynski family in the 16th century, based on the records of the Sanok castle (grod) and land courts. The methodology of the research is based on the principles of scientific criticism, historicism, as well as on the use of general scientific (analysis, synthesis, generalization) and specific historical (historical typological, historical systemic, prosopographic, microhistorical) methods. Conclusions. Vladyslav (also known as Wacław) Pobidynski (1470 – † ar. 1499), the descendant of the Pobidynski family, carried on the lineage in the 16th century. The family experienced demographic growth due to large offspring in multiple family branches during this period. The Sanok castle and land court records provide information on 57 individuals from the Pobidynski family, who lived during the 16th century, in contrast to only 36 identified for the 15th century. However, the family’s landholdings did not expand accordingly. On the contrary, estates were increasingly divided among numerous heirs, resulting in smaller and less economically viable shares. This marks a stark contrast to the 15th century, when the family’s property base grew significantly in each generation. The weakening of the family’s economic standing appears to have affected their social status. In the local administrative hierarchy of the 16th century, only three family members held official positions: Yan Pobidynski (1500 – †1527/1529), who served as Deputy Judge and later Land Judge of Sanok land; his brother Klemens Pobidynski (1483 – † before 1526), who was the Castle Judge and Wacław, the son of Stanisław Pobidynski (1541 – 1581), who served as Deputy Judge and Vice-starosta of Sanok land. Despite their declining material base, the Pobidynski family remained active in legal and economic matters, acting as creditors and borrowers, and maintained their place within the local nobility through kinship ties and regular participation in local assemblies (sejmik) and court sessions as assessors. Key words: Sanok land, the Pobidynski family, nobility, castle (grod) court, land court, economic matters, creditors, borrowers, debtors.